Diversity of Tidal Swamp Rice (Oryza sativa) Cultivars Indigenously from South Kalimantan, Indonesia - Dindin Hidayatul Mursyidin; Muhammad Zia Zul Haq; Badruzsaufari Badruzsaufari (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Studies on genetic diversity and relationships are necessary for breeders and scientists to increase the effectiveness of future breeding programs. The tidal swamp rice (Oryza sativa L.) is one of the potential germplasms which has a prominent opportunity to be incorporated in the rice breeding program. This study aimed to investigate and reveal the genetic diversity and relationship of tidal swamp rice germplasms indigenously from South Kalimantan, Indonesia, using Random Amplified Polymorphic DNA (RAPD) markers. A total of ten rice samples, consisting of nine from this region and one from South Sumatera (an outgroup), and five selected RAPD markers, i.e., OPB-06, OPAJ-01, OPAB-17, OPAL-09, and OPAL-08, were used in this study. DNA amplifications were performed and programmed for one cycle of initial denaturation (5 min, 94ºC), 45 cycles of denaturation (30 sec, 94ºC), annealing (30 sec, 37ºC), and extension (1.5 min, 72ºC), as well as one cycle of final extension (7 min, 72ºC). The genetic similarity was analyzed using Dice’s coefficient method, whereas their relationship (dendrogram) by the UPGMA. The results showed that these germplasms have a moderate genetic diversity level, indicated by the polymorphism degree of 75.64%. The clustering analysis revealed that they are grouped into three main groups at a similarity coefficient of 0.70. In this case, Siam Unus is distantly related to the other cultivars and forms a solitaire group. Siam Unus also shows the farthest relationship with Sardani, an outgroup. It is a new finding for the genetic insight of tidal swamp rice of South Kalimantan, Indonesia, including their diversity and relationship. Thus, the results obtained from this study is useful in supporting future rice conservation and breeding programs.